Learning Basic Mathematical Functions with Augmented Reality - Cerqueira, José (2020)
This article presents the development of a serious game targeting secondary school students, that uses Augmented Reality (AR) to visualize, manipulate and explore mathematical concepts, particularly linear, quadratic, exponential and trigonometric (sine and cosine) functions. The motivation behind the development of the AR application was to provide students with learning materials that facilitate the exploration of a mathematical subject that is often considered difficult to learn. Whereas traditional resources for teaching and learning mathematics use manuals and scientific calculators to solve problems, the application, named FootMath, simulates a 3D football game, where the users can manipulate and explore the different functions using parameters with different values to score goals. Additionally, we discuss the potential of AR games as educational and engaging tools that can be used to facilitate learning, especially problem based learning and logical reasoning.